The PEMBERDAYAAN MASYARAKAT BANJAR SILAKARANG MELALUI KKN TEMATIK BERBASIS TRI HITA KARANA - Ni Komang Sariasih; Ni Luh Gede Liswahyunigsih; I Ketut Muada; I Made Saputra Ardinata; I Nyoman Erpi Sudarma (Sewagati, 2026)
The Thematic Community Service Program (KKN) Group 4 of Universitas PGRI Mahadewa Indonesia took place in Banjar Silakarang, Singapadu Kaler Village, Sukawati District, Gianyar Regency, Bali, from February 18 to March 15, 2026. Carrying the theme "Increasing Community Capacity Through Digital Education, Environmental Management, and Socio-Cultural Strengthening", this program combines the provision of hygiene facilities, socialization on organic waste management with biopore techniques and inorganic waste management through a waste bank system, digital-based population data collection, naming of road sections, and support for youth arts and cultural activities. The participatory method involved the banjar government, PKK groups, the younger generation, and the community as a whole, based on the Tri Hita Karana philosophy (Parahyangan, Pawongan, Palemahan). The results of this program showed increased environmental awareness, efficiency of banjar administration, and strengthening of socio-cultural relations. This program also helps in the development of a sustainable banjar community in accordance with Balinese local wisdom.